Efficiency and safety of cannabinoid medical use: an analysis of discussions and observed trends on Instagram - Litvinova, Olena; Baral, Bikash; Wochele-Thoma, Thomas; Matin, Maima; Tzvetkov, Nikolay T.; Adamska, Olga; Kamińska, Agnieszka; Łapiński, Marcin; Stolarczyk, Artur; Atanasov, Atanas G. (Frontiers in Public Health, 2024)
BackgroundCannabis and its derivatives show encouraging therapeutic effects in the treatment of various diseases. However, further studies are needed to better assess their efficacy and safety. A promising base for research in the field of medicine and additional pharmacovigilance is social networks, in which experience and knowledge are exchanged between researchers, doctors, and patients, as well as information about the potential risks and benefits of using drugs for medical purposes is disseminated. The aim of this study was to investigate the reported efficiency and safety of medical use of cannabinoids in patients using posts on the social media Instagram and analyze the observed trends.MethodsSocial media listening platform Apify was used to collect data with hashtags as of June 4, 2024, including posts from 2023 and 2024, with some data extending into later periods, in compliance with a systematic approach to data collection. The analysis of the data obtained from the research was conducted using the RStudio platform.ResultsThe analysis covered 1,466 posts containing hashtags related to cannabinoids. The posts studied were categorized as follows: 33.08% focused on advertising and commercialization, 25.58% on personal experience, 21.35% on other topics, and 19.99% contained educational content. An analysis of overall content relevance found that the majority of Instagram posts (81.79%) related to cannabis and cannabinoid hashtags are relevant. Most of the Instagram posts studied were posters, followed by personal photos and videos. The analysis shows that English dominates the studied category (70.74% of posts), while German, French, Spanish, and other languages also occupy a significant place, emphasizing the importance of a multilingual approach in content analysis. It has been revealed that organizations publish a larger percentage of posts under this study, with a higher percentage of relevance. Personal experience stories receive a significant number of “likes” indicating a strong emotional connection between audience and content. Instagram discussions about cannabinoid treatment support evidence from scientific studies about their effectiveness in treating a range of diseases, such as epilepsy with Lennox–Gastaut and Dravet syndromes, multiple sclerosis, cancer, and HIV-cachexia, nausea and vomiting caused by chemotherapy. At the same time, they emphasize the need for further clinical studies to better assess safety, side effects, and optimal dosages. Advertising and commercial posts can contribute to increased cannabis use, highlighting the need to raise awareness of risks and strengthen preventive measures.ConclusionAnalysis of content on the social media Instagram can complement traditional scientific research by providing information on the real use of cannabis and its derivatives, contributing to the development of safe and effective recommendations for its use.